2017
DOI: 10.4236/tel.2017.74058
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Financial Development on the Transmission of Monetary Policy

Abstract: This paper looks at the effect of financial development on output and bank liquidity by doing a cross-country analysis of 119 countries across 18 years from 1997-2014. We develop three hypotheses by combining multiple strands of literature which have heretofore existed in parallel. The main research question is whether financial development serves to provide greater bank liquidity and whether it does indeed stimulate output growth. This question is of particular relevance when there are changes in monetary pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
(39 reference statements)
0
12
0
Order By: Relevance
“…There is a different effect of FD on MPE in developing countries relative to advanced ones, in which the inflation rate has increased in response to FD in advanced countries, whereas output declines with FD in developing economies. Seth and Kalyanaraman (2017) found that the effect of monetary policy is strengthening in response to the level of FD in advanced economies. However, the effect of monetary policy is less in poor countries, possibly because of the lower number of financial intermediaries available to assist in the delivery of monetary policy.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a different effect of FD on MPE in developing countries relative to advanced ones, in which the inflation rate has increased in response to FD in advanced countries, whereas output declines with FD in developing economies. Seth and Kalyanaraman (2017) found that the effect of monetary policy is strengthening in response to the level of FD in advanced economies. However, the effect of monetary policy is less in poor countries, possibly because of the lower number of financial intermediaries available to assist in the delivery of monetary policy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is because the fast growth of the financial system has a direct impact on the monetary policy set by the Central Bankers in Given this backdrop, this paper contributes to the existing literature in FD and MPE in several ways. First, some studies, for example, Carranza et al (2010), Ma and Lin (2006) and Seth and Kalyanaraman (2017), have examined the relationship between FD and MPE in cross-countries using panel data analysis. However, the previous study cannot formulate the role of financial sector development on MPE for an individual country perspective.…”
mentioning
confidence: 99%
“…This research interest has been kindled mostly by the notion that "finance leads growth"a hypothesis that seems to be winning the argument with most economists, despite the fact that the debate on the finance-growth nexus still rages on. Over the years, a number of studies that are devoted to financial development has identified its level as a key ingredient in the pursuit of economic agendas, including policy effectiveness (Gigineishvili, 2011;Seth and Kalyanaraman, 2017). According to Aghion et al (2009), financial development is beneficial to economic performance at sufficiently high levels.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, a central bank is deemed credible when it delivers its stated inflation objective. As institutional and financial strength improves, so does the transmission of monetary-policy action (Seth & Kalyanaraman, 2017). Institutional strength and policy credibility in EMEs still tend to be weaker than in their advanced counterparts.…”
Section: Literature Reviewmentioning
confidence: 99%